Strengthening MSME Marketing through Digital Marketing: International Community Service in Thailand among OTOP Entrepreneurs - Syafei, M. Yani; Wahdiniwaty, Rahma; Rael Astillero, Marlon; Fakbua, Nidanuch; Tribuana, Dhimas; Hermawan, Budi; Swastika Gusti Krisna Dewi, Puri (PT Inovasi Pratama Internasional, 2025)
This international community service program was conducted on August 26, 2025, at the Bang Prong Subdistrict Administrative Organization Office, Samut Prakan, Thailand, with the main objective of strengthening the capacity of OTOP MSME entrepreneurs through the use of digital marketing. The implementation method included product exhibitions, production process demonstrations, and interactive training sessions on digital marketing strategies, social media utilization, and promotional content creation. The results indicated significant improvements in participants’ awareness, skills, and confidence in applying digital technologies to their businesses. The activity also enhanced cross-cultural collaboration between Indonesian and Thai higher education institutions and created opportunities for sustainable development supported by institutional and digital infrastructure. In conclusion, this program highlights the importance of international collaborative community service models in accelerating the digital transformation of MSMEs.